PENGARUH SALINITAS BERBEDA TERHADAP KULTUR PAKAN ALAMI Thalassiosira sp. SKALA INTERMEDIET - Subhan, Rio Yusufi; Verdian, Aldi Huda; Muahirin, Ronal (Politeknik Negeri Lampung, 2023)
Thalassiosira sp. is a natural feed that has high nutritional content and supports the growth of Litopenaeus vannamei larvae. This research aims to determine cell density, peak population, daily growth rate, and water quality parameters on intermediate scale culture of Thalassiosira sp. with different salinities. This research was conducted at CV. Manunggal Rasa by applying 28 ppt, 30 ppt, and 32 ppt salinity with two repetition. The highest peak population was found in the 28 ppt salinity treatment with an average number of 40×104 cells/ml and the lowest population was in the 32 ppt salinity treatment with an average number of 35.5×104 cells/ml. The daily growth rate reached the highest level in the treatment with 28 ppt salinity with a value of 0.28 cells/ml/day. Meanwhile, the 32 ppt salinity treatment had the lowest daily growth rate 0.14 cells/ml/day. The population peak occurred on the third day, after which there was a decrease in the number of Thalassiosira sp. cell populations. The results of this research indicate that the higher the salinity will reduce the results of the parameters tested.